2021
DOI: 10.4236/as.2021.123019
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic Performance and Potency of <i>Cannabis sativa</i> L. Grown under LED and HPS Illumination

Abstract: Light-emitting diodes (LEDs) can be used as an energy efficient alternative to high-pressure sodium (HPS), which have historically been the standard for supplemental lighting in cannabis cultivation. However, there is a lack of scientific understanding in the cannabis industry regarding plant physiology, which has resulted in the adoption of cannabis cultivation methods based on hearsay rather than scientific research. The goals of this study were to 1) compare LED lighting options that are commonly used in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…In this study, pre-treatment net photosynthetic rates (Leaf-A N μmol·m −2 ·s −1 ) were similar for all chemotypes during early flower, mid-flower, and late flower with means between 20 and 30 μmol·m −2 ·s −1 (Figure 1(a)). These results were generally consistent with trends of other studies [6] [7] [13] [16] [17] [21]; although photosynthetic rates in this study were enhanced compared to most published cannabis photosynthetic research. For example, Chandra et al 2008 observed the maximum rate of photosynthesis of 24.60 μmol·m −2 ·s −1 at 1500 PPFD at atmospheric CO 2 350 ± 5 µmol·mol −1 .…”
Section: Discussionsupporting
confidence: 93%
“…In this study, pre-treatment net photosynthetic rates (Leaf-A N μmol·m −2 ·s −1 ) were similar for all chemotypes during early flower, mid-flower, and late flower with means between 20 and 30 μmol·m −2 ·s −1 (Figure 1(a)). These results were generally consistent with trends of other studies [6] [7] [13] [16] [17] [21]; although photosynthetic rates in this study were enhanced compared to most published cannabis photosynthetic research. For example, Chandra et al 2008 observed the maximum rate of photosynthesis of 24.60 μmol·m −2 ·s −1 at 1500 PPFD at atmospheric CO 2 350 ± 5 µmol·mol −1 .…”
Section: Discussionsupporting
confidence: 93%
“…Wei and colleagues [95] observed higher flower and CBD yields when using two types of LEDs than when using HPS lamps, but the LED light intensity was higher (540 and 552 µmol m −2 s −1 ) than the HPS intensity (191 µmol m −2 s −1 ). In another study, higher THC production was observed in plants grown under LED light than HPS lamps [96]. One of the difficulties in evaluating the influence of light quality is the need to standardize the light intensity and spectra (only varying the spectrum that is evaluated).…”
Section: Effects Of Lightmentioning
confidence: 99%
“…Light is the unique source of energy for photosynthesis and acts as a driving force for plant growth. The quality, quantity and duration of light are useful input materials that regulate not only the growth and development of plants but also ensure their sustainable production under environmental conditions (Jenkins and Livesay, 2021). Growing plants under artificial light allow growers to maintain horticultural traits, including plant morphology, growth habits, flowering, quality and endpoint plant productivity (Rodriguez-Morrison et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Light systems for cannabis cultivation need to ensure quality and quantity to maximize plant productivity and achieve a high level of secondary metabolite production (Jenkins and Livesay, 2021). The quality and intensity of light should consider the physiological and photosynthetic enhancement to ensure maximum, uniform, and consistent productivity with minimum deleterious effects of high leaf temperature (Greer et al, 1986) and photooxidative damage (Demmig-Adams and Adams Iii, 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation